A case of autosomal recessive hypercholesterolemia caused by a new variant in the LDL receptor adaptor protein 1 gene - Vaverkova, Helena; Tichy, Lukas; Karasek, David; Freiberger, Tomas (Journal of clinical lipidology, 2019)
We report a new variant in the LDLRAP1 gene associated with autosomal recessive hypercholesterolemia in a woman of central European ancestry.
Keywords: Female; lidé středního věku; Ezetimibe; genetická variace; Genetic Variation; mužské pohlaví; heterozygot; PCSK9 inhibitors; Humans; dospělí; Hyperlipoproteinemia Type III; Hypercholesterolemia; Adaptor Proteins, Signal Transducing; rodokmen; Statins; Heterozygote; Pedigree; lidé; Clinical phenotype; Middle Aged; LDL apheresis; Autosomal recessive hypercholesterolemia; Lipid lowering therapy; senioři; hypercholesterolemie; hyperlipoproteinemie typ III; ženské pohlaví; Aged; LDLRAP1; Adult; Male; adaptorové proteiny signální transdukční